USING LOCAL COMMON VETCH (VICIA SATIVA) IN POULTRY RATION - Ibrahim Said Ibrahim Kloor (Mesopotamia Journal of Agriculture)
The study was carried out in the farm of the poultry, college of agriculture & Forestry, Mosul university to study the effect of using different organic compounds to detoxification local common vetch for broiler chickens, 160 one day old chicks (cobb) were used distributed into four treatments, (40 chicks/ treatment) the first is control (without vetch), the second treatment contained 20% raw vetch, the third treatment contained 20% raw vetch added 20gm S. cerevisiae/Kg feed and the fourth treatment contained 20% raw vetch added 5 mg activated charcoal/Kg feed. All treatments are isocaloric and isonitrognous. The toxic effect of the vetch were reduced by adding S.cerevisiae to the ration in the third treatment, which is represented by significant increase in live body weight (4 and 7 weeks), improved feed intake and feed conversion efficiency, a significant decrease in the total mortality percent and this finally leads to a significant improvement in production index compared to the birds which fed the raw vetch ration. Also adding S.cerevisiaa to ration were significantly reduced the relative weights of liver, it is revealed that adding the activated charcoal to ration containing 20% vetch had no detrimental effect on detoxification of common vetch.